Мотивация и стимулирование как эффективный метод управления персоналом - Матросов, Александр Дмитриевич; Большаков, Дмитрий Витальевич (НТУ "ХПИ", 2015)
В статье рассматриваются такие категории в управлении персоналом, как "мотивация" и "стимулирование трудовой деятельности", раскрывается роль стимулирования мотивации работников в функционировании эффективной системы управления персоналом, вносятся авторские предложения и рекомендации по совершенствованию данных процессов. Приведены понятия, основные концепции, обосновывается цель деятельности по мотивации и стимулированию, роль руководителя в управлении мотивацией и стимулированием.

The article deals with such categories in personnel management as "motivation" and "work incentives", explores the role of in centives to motivate employees in an effective personnel management system, introduced the author's suggestions and recommendations for improvement of these processes. We present the concept, the basic concept is justified by objective of motivating and encouraging the role of leader in the management of motivation and encouragement. To develop and implement new motivational systems directly in the organizations (enterprises), allow to involve a greater degree of new highly skilled professionals able to manage both small and large groups, focusing mainly on the individual with the motivation in accordance with the quantity and quality of the employee.
Motivation and stimulation as an effective method of personnel management
Keywords: работник; руководитель; мотивирующие факторы; employee; manager; motivating factors